PREVENTING BIAS IN THE ASSESSMENT PROCESS THROUGH A DOUBLE-BLIND APPROACH - Wulandari, Puti Rizka (Jurnal Kajian Pendidikan dan Psikologi, 2026)
Bias prevention in the assessment process is often underestimated. The purpose of this study is to examine strategies for preventing bias in the assessment process through a double-blind approach. This study employed a literature review method using various sources related to assessment bias and the double-blind approach. The findings indicate that bias in the assessment process can be reduced through several double-blind strategies designed to minimize the influence of evaluator subjectivity, such as concealing the identities of both students and assessors, as well as organizing anonymous evaluation procedures. This approach helps enhance the objectivity and validity of assessment outcomes, although it requires adjustments and adequate system support to be implemented effectively. These findings provide important recommendations for educational practitioners to adopt double-blind strategies in order to create a fairer and more professional assessment process.